Penjadwalan Tenaga Kerja Pada Hotel Menara Lexus Menggunakan Algoritma Genetika - Rohima Almahuwanah; Sajaratud Dur; Hendra Cipta (Lembaga Pengembangan Kinerja Dosen, 2024)
Labor scheduling is allocating human resources to work stations according to needs. To increase productivity, companies must schedule labor optimally. In allocating labor, the Hotel Menara Lexus company has implemented labor scheduling with 3 work shifts, namely morning, afternoon and night. Because scheduling is still made manually, it is possible for schedule